Clinical and histopathological characteristics of 611 patients with basal cell carcinoma - Qifeng LI; Jihong WANG; Jinfang ZHANG; Kaixin WANG; Dingheng ZHU; Ruzeng XUE (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2021)
Objective: To analyze the clinicopathological characteristics of skin basal cell carcinoma, so as to improve the coincidence rate of clinical diagnosis and provide basis for early diagnosis, treatment and prognosis. Methods: The clinical and pathological features of 611 patients with basal cell carcinoma diagnosed by primary biopsy in Dermatology Hospital, Southern Medical University from March 2014 to February 2021 were retrospectively analyzed. Results: There were 268 males and 343 females in 611 patients, the ratio of male to female was 1 ∶1.28; the onset age was 19~92 (64.18±13.90) years old. There were 296 cases (48.45%) with mass, nodule and tumor, 248 cases (40.59%) with patch and papule, and 67 cases (10.97%) with erosion or ulcer, scar and cyst. Pathological classification: nodular type 377 cases (61.71%), infiltrative type 85 cases (13.92%), superficial type 69 cases (11.30%), other types 80 cases (13.10%). Clinical misdiagnosis rate was 16.86%. Conclusions: The main clinical manifestation is mass, and the main pathological type is nodule. It is important to improve the diagnosis, treatment and prognosis of BCC by improving the rate of skin biopsy and strengthening the understanding of easily misdiagnosed lesions.